Key Determinants Shaping Farmers’ Satisfaction with Site‑Speciϐic Fertilizer Recommendations (SSFR) in Ethiopia - Adimassu, Zenebe; Mesfin, Tewodros; Tibebe, Degefie; Tilaye, Amsalu; Ebrahim, Mohammed; Abera, Wuletawu; Tamene, Lulseged (2025)
This study assessed farmers' satisfaction with site-specific fertilizer recommendations (SSFR) and identified key determinants influencing their satisfaction in Ethiopia. Data from 202 households, selected through stratified random sampling, was analyzed using Principal Component Analysis (PCA) and Ordered Probit Model. Results show that 58.4% of farmers were satisfied with the quantity, while 56.9% were satisfied with the timing of fertilizer application in the study areas. Strong satisfaction was reported by 37.6% for recommended fertilizer rates and 39.6% for timing, with minimal (4%) dissatisfaction. Partnerships between the Ministry of Agriculture (MoA), LERSHA, and Digital Green reveals varying satisfaction level had varied satisfaction rates, with MoA leading at 44.6%, compared to LERSHA’s 24.8% and Digital Green’s 30.7%. The study identified key factors that affect satisfaction, including, education level, farm size, availability and affordability of SSF recommendations, the quality of information on planting time, information on land preparation, use of SMS for SSFR dissemination, recommendation of SSFR using cluster approach and livestock size. Higher education levels and larger farms are linked to better SSFR application. Participation in cluster recommendation units fosters collective learning and enhances satisfaction, while access to affordable and timely SSF recommendation improves implementation and crop yields. Short Message Services (SMS) communication has proven effective in engaging farmer and enhancing satisfaction. As Ethiopia continues to work towards agricultural modernization and sustainability, addressing these factors will be vital for promoting the use of site-specific fertilizers (SSF) across Ethiopia's diverse farming landscapes.